Da'wa: A Global History of Islamic Missionary Thought and Practice - Kuiper, Matthew J. (The New Edinburgh Islamic Surveys, 2021)
In this engaging study, Matthew J. Kuiper tells the fascinating story of how Islam became a world religion and cultural phenomenon of immense scale, astonishing diversity and global impact. His starting point is the dramatic upsurge in da'wa: 'inviting' to Islam, or Islamic missionary activism.